2019
DOI: 10.32479/ijeep.8694
|View full text |Cite
|
Sign up to set email alerts
|

Experimenting the Long-Haul Association Between Components of Consuming Renewable Energy: Ardl Method With Special Reference to Malaysia

Abstract: Global warming is a standout amongst the present most critical environmental issues, caused generally by emission of greenhouse gases, for example, carbon dioxide from the consuming of fossil fuels. Emissions of carbon dioxide fluctuate all through nations in Asia. It is progressively perceived that nations must act to advance the more prominent utilization of renewable energy resources as a component of activities looking to relieve environmental change. This paper shows a survey of the energy request situati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Belt Road countries were investigated by [110,111], SAARC and ASEAN countries [112], as well as, South Korea [113], Bangladesh [114], Malaysia [115][116][117][118], Indonesia [119][120][121][122][123], Vietnam [124], Taiwan [125], Pakistan [126][127][128][129][130], Kazakhstan [131,132], and Thailand [133]. Not many studies dealing with the African continent [134] investigate the continent, [135] sub-Saharan Africa, [136] Rwanda, [137] Cameron, Nigeria [138], [139] Ethiopia and [140] Tunisia.…”
Section: Discussionmentioning
confidence: 99%
“…Belt Road countries were investigated by [110,111], SAARC and ASEAN countries [112], as well as, South Korea [113], Bangladesh [114], Malaysia [115][116][117][118], Indonesia [119][120][121][122][123], Vietnam [124], Taiwan [125], Pakistan [126][127][128][129][130], Kazakhstan [131,132], and Thailand [133]. Not many studies dealing with the African continent [134] investigate the continent, [135] sub-Saharan Africa, [136] Rwanda, [137] Cameron, Nigeria [138], [139] Ethiopia and [140] Tunisia.…”
Section: Discussionmentioning
confidence: 99%
“…Improved legal safeguards encourage renewable energy companies to boost their output of green power. Roespinoedji (2019) found that FDI and GDP expanded renewable power production in Malaysia. Kang et al (2021) analyzed how GDP, FDI, trade openness, and urbanization contributed to the determination of renewable energy in South Asian countries from 1990 to 2019.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Roespinoedji et al (37) utilized a combination of ARDL and VECM for examining the elements influencing renewable electricity consumption in Malaysia. The results indicated that financial development and foreign direct investment are the real drivers for renewable energy consumption.…”
Section: Vector Error-correction Modelsmentioning
confidence: 99%